2020
DOI: 10.3389/fmars.2020.00257
|View full text |Cite
|
Sign up to set email alerts
|

Pelagic Habitat Partitioning of Late-Larval and Juvenile Tunas in the Oceanic Gulf of Mexico

Abstract: Sampling and Analysis Program; S EPI, minimum salinity in the epipelagic zone; T EPI , maximum temperature (• C) recorded in the epipelagic zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Spawning activity of A. thazard seems to favor more productive continental shelf and slope environments, and during spring-summer the intrusion of deeper and more nutritious waters of the SACW causes an enrichment of the habitat's productivity and enables the feeding and growth of larvae and adults (Valentin, 2001;Pruzinsky et al, 2020). This characteristic was also observed by Bahou et al ( 2016) in Côte d'Ivoire, as peak spawning season occurred during main upwelling season.…”
Section: Reproductive Cyclementioning
confidence: 62%
“…Spawning activity of A. thazard seems to favor more productive continental shelf and slope environments, and during spring-summer the intrusion of deeper and more nutritious waters of the SACW causes an enrichment of the habitat's productivity and enables the feeding and growth of larvae and adults (Valentin, 2001;Pruzinsky et al, 2020). This characteristic was also observed by Bahou et al ( 2016) in Côte d'Ivoire, as peak spawning season occurred during main upwelling season.…”
Section: Reproductive Cyclementioning
confidence: 62%
“…Anyway, in the GOM, their condition of visual predators might also limit their vertical expansion. Horizontal habitat segregation in scombrid larvae has already been documented in the Pacific [8], in the GOM [23] and in the MED [51]. It is to be expected that the same segregation can occur in the vertical distribution of taxa if the environmental conditions are within the taxa specific limits.…”
Section: Discussionmentioning
confidence: 89%
“…As such, temperature is one primary variable explaining the worldwide distribution of major tuna spawning areas [18,19] and recruitment variability [20]. Other environmental variables such as salinity and fluorescence explain larval spatial segregation of tuna species at a small spatial scale [8,14,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In the CR was not significant for expansion. In this context, several studies in the Gulf of Mexico demonstrated that at larval stage BFT is the pelagic species most common of Scombridae (Cornic and Rooker, 2018, Pruzinsky et al, 2020).…”
Section: Discussionmentioning
confidence: 99%